Nuclear Deformation Predicts Alpha Decay Behavior in Superheavy Elements: Deformasi Nuklir Memprediksi Perilaku Peluruhan Alfa pada Elemen Super Berat - Ghazi , Hanan Kaayem (Academia Open, 2025)
General Background: Alpha decay is a dominant decay mode in superheavy elements (SHEs), offering critical insights into nuclear structure and stability. Specific Background: Elements with atomic numbers Z = 114–118 exhibit significant nuclear deformation, affecting their decay characteristics. Knowledge Gap: Existing models often assume spherical symmetry, leading to inaccurate half-life predictions due to neglecting deformation effects. Aims: This study quantifies the influence of nuclear deformation on alpha decay properties in SHEs, refining theoretical models for more accurate predictions. Results: By integrating deformation-dependent Woods-Saxon potentials and modifying the Geiger-Nuttall law within a WKB framework, the study achieved a 21.1% mean absolute error—improving prediction accuracy. Strong inverse correlations between quadrupole deformation (β₂) and half-life were observed; for example, Oganesson-294 (β₂ = 0.24) showed a 50% shorter half-life than spherical-based predictions. Novelty: The study combines deformation parameters (β₂, β₄), FRDM and WS4 models, and experimental validation from leading SHE laboratories, demonstrating the essential role of nuclear shape in decay behavior. Implications: These findings support the "island of stability" hypothesis near Z = 114–116 and underscore the necessity for deformation-inclusive models and advanced density-functional theory to enhance the understanding and synthesis of future SHEs. Highlights: Deformation lowers Coulomb barrier, increasing alpha decay probability. Modified models improve half-life prediction accuracy. Supports stability near Z = 114, N = 1 Keywords: Alpha decay, superheavy elements, nuclear deformation, half-life prediction, island of stability